Comparative analysis of medicinal plant Isodon rubescens and its common adulterants based on chloroplast genome sequencing - Zhou, Zhongyu; Wang, Jing; Pu, Tingting; Dong, Jingjing; Guan, Qin; Qian, Jun; Shi, Linchun; Duan, Baozhong (Frontiers in Plant Science, 2022)
Isodon rubescens (Hemsley) H. Hara is the source of Donglingcao under the monograph Rabdosiae Rubescentis Herba in Chinese Pharmacopoeia. In the local marketplace, this medicine can be accidentally contaminated, deliberately substituted, or mixed with other related species. The contaminants of herbal products are a threat to consumer safety. Due to the scarcity of genetic information on Isodon plants, more molecular markers are needed to avoid misidentification. In the present study, the complete chloroplast genome of seven species of Isodon was sequenced, de novo assembled and characterized. The cp genomes of these species universally exhibited a conserved quadripartite structure, i.e., two inverted repeats (IRs) containing most of the ribosomal RNA genes and two unique regions (large single copy and small single copy). Moreover, the genome structure, codon usage, and repeat sequences were highly conserved and showed similarities among the seven species. Five highly variable regions (trnS-GCU-trnT-CGU, atpH-atpI, trnE-UUC-trnT-GGU, ndhC-trnM-CAU, and rps15-ycf1) might be potential molecular markers for identifying I. rubescens and its contaminants. These findings provide valuable information for further species identification, evolution, and phylogenetic research of Isodon.